Solve for x x/3-x=6

Math
x3-x=6
Simplify x3-x.
Tap for more steps…
To write -x as a fraction with a common denominator, multiply by 33.
x3-x⋅33=6
Simplify terms.
Tap for more steps…
Combine -x and 33.
x3+-x⋅33=6
Combine the numerators over the common denominator.
x-x⋅33=6
x-x⋅33=6
Simplify the numerator.
Tap for more steps…
Factor x out of x-x⋅3.
Tap for more steps…
Raise x to the power of 1.
x1-x⋅33=6
Factor x out of x1.
x⋅1-x⋅33=6
Factor x out of -x⋅3.
x⋅1+x(-1⋅3)3=6
Factor x out of x⋅1+x(-1⋅3).
x(1-1⋅3)3=6
x(1-1⋅3)3=6
Multiply -1 by 3.
x(1-3)3=6
Subtract 3 from 1.
x⋅-23=6
x⋅-23=6
Simplify the expression.
Tap for more steps…
Move -2 to the left of x.
-2⋅x3=6
Move the negative in front of the fraction.
-2×3=6
-2×3=6
-2×3=6
Multiply both sides of the equation by -32.
-32⋅(-2×3)=-32⋅6
Simplify both sides of the equation.
Tap for more steps…
Simplify -32⋅(-2×3).
Tap for more steps…
Cancel the common factor of 3.
Tap for more steps…
Move the leading negative in -32 into the numerator.
-32⋅(-2×3)=-32⋅6
Move the leading negative in -2×3 into the numerator.
-32⋅-2×3=-32⋅6
Factor 3 out of -3.
3(-1)2⋅-2×3=-32⋅6
Cancel the common factor.
3⋅-12⋅-2×3=-32⋅6
Rewrite the expression.
-12⋅(-2x)=-32⋅6
-12⋅(-2x)=-32⋅6
Cancel the common factor of 2.
Tap for more steps…
Factor 2 out of -2x.
-12⋅(2(-x))=-32⋅6
Cancel the common factor.
-12⋅(2(-x))=-32⋅6
Rewrite the expression.
-1⋅(-x)=-32⋅6
-1⋅(-x)=-32⋅6
Multiply.
Tap for more steps…
Multiply -1 by -1.
1⋅x=-32⋅6
Multiply x by 1.
x=-32⋅6
x=-32⋅6
x=-32⋅6
Simplify -32⋅6.
Tap for more steps…
Cancel the common factor of 2.
Tap for more steps…
Move the leading negative in -32 into the numerator.
x=-32⋅6
Factor 2 out of 6.
x=-32⋅(2(3))
Cancel the common factor.
x=-32⋅(2⋅3)
Rewrite the expression.
x=-3⋅3
x=-3⋅3
Multiply -3 by 3.
x=-9
x=-9
x=-9
Solve for x x/3-x=6

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top